The Perfect Way to Predict the Severity of Acute Pancreatitis: The Search Continues - Daniel C Sadowski (Canadian Journal of Gastroenterology)
This study was designed to determine the clinical utility of three rating scales (Ranson's, Acute Physiology And Chronic Health Evaluation [APACHE] II and Glasgow) in predicting the severity of acute pancreatitis experienced by patients known to have human immunodeficiency virus (HIV) or acquired immunodeficiency syndrome (AIDS). A retrospective analysis identified 73 patients with both acute pancreatitis and HIV who had been admitted to two Canadian hospitals between 1989 and 1999. Of those 73, 11 (15%) went on to have a clinical course consistent with a diagnosis of severe pancreatitis. For the purposes of the study, severe pancreatitis was defined by the occurrence of death, intensive care unit admission, surgical intervention or significant symptomatic local complications (necrosis, abscess or pseudocyst). The authors found that the APACHE II and Ranson's scores had a sensitivity of 100% and specificities of 70% and 33% for severe pancreatitis, respectively. The Glasgow score had a statistically poorer diagnostic performance.